Learn What Is The Missing Term 10x 4x2 7x 3x 6x2

from a handpicked tutor in LIVE 1-to-1 classes

from a handpicked tutor in LIVE 1-to-1 classes

# What is the missing term? (10x - 4x^{2}) - (7x + ?) = 3x - 6x^{2}

**Solution:**

Given, (10x - 4x^{2}) - (7x + ?) = 3x - 6x^{2}

We have to find the missing term.

Let the missing term be a.

So, (10x - 4x^{2}) - (7x + a) = 3x - 6x^{2}

10x - 4x^{2} - 7x - a = 3x - 6x^{2}

Grouping of common terms,

10x - 7x - 3x - a = -6x^{2} + 4x^{2}

10x - 10x - a = -2x^{2}

- a = -2x^{2}

a = 2x^{2}

Therefore, the missing term is 2x^{2}.

## What is the missing term? (10x - 4x^{2}) - (7x + ? ) = 3x - 6x^{2}

**Summary:**

The missing term of the equation (10x - 4x^{2}) - (7x + ?) = 3x - 6x^{2} is 2x^{2}.

Math worksheets and

visual curriculum

visual curriculum